2022
DOI: 10.3390/ijms23042201
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Antiremodeling Effects of Losartan, Mirabegron and Their Combination on the Development of Doxorubicin-Induced Chronic Cardiotoxicity in a Rat Model

Abstract: Despite the effectiveness of doxorubicin (DOXO) as a chemotherapeutic agent, dose-dependent development of chronic cardiotoxicity limits its application. The angiotensin-II receptor blocker losartan is commonly used to treat cardiac remodeling of various etiologies. The beta-3 adrenergic receptor agonist mirabegron was reported to improve chronic heart failure. Here we investigated the effects of losartan, mirabegron and their combination on the development of DOXO-induced chronic cardiotoxicity. Male Wistar r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 76 publications
0
23
0
1
Order By: Relevance
“…Indeed, TGF-β1 has a controversial role in the pathogenesis of ulcerative colitis ( Feagins, 2010 ; Ihara et al, 2017 ), yet it was here part of the pathomechanism. The anti-fibrotic potential of the tested drugs has been reported earlier in non-ulcerative colitis models; first, carvedilol was able to decrease TGF-β1/α-SMA and increase SMAD-7 in renal ( Wong et al, 2001 ) and hepatic ( El-Wakeel et al, 2018 ) injury models, whereas mirabegron proved its anti-fibrotic potential against doxorubicin-induced cardiotoxicity via the inhibition of TGF-β/SMAD2/3 pathway ( Freiwan et al, 2022 ). However, the aptitude of mirabegron to release noradrenaline ( Mo et al, 2017 ) may also be one possible reason behind the augmentation of SMAD-7 ( Kanamaru et al, 2001 ).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Indeed, TGF-β1 has a controversial role in the pathogenesis of ulcerative colitis ( Feagins, 2010 ; Ihara et al, 2017 ), yet it was here part of the pathomechanism. The anti-fibrotic potential of the tested drugs has been reported earlier in non-ulcerative colitis models; first, carvedilol was able to decrease TGF-β1/α-SMA and increase SMAD-7 in renal ( Wong et al, 2001 ) and hepatic ( El-Wakeel et al, 2018 ) injury models, whereas mirabegron proved its anti-fibrotic potential against doxorubicin-induced cardiotoxicity via the inhibition of TGF-β/SMAD2/3 pathway ( Freiwan et al, 2022 ). However, the aptitude of mirabegron to release noradrenaline ( Mo et al, 2017 ) may also be one possible reason behind the augmentation of SMAD-7 ( Kanamaru et al, 2001 ).…”
Section: Discussionmentioning
confidence: 76%
“…Frontiers in Pharmacology frontiersin.org mirabegron proved its anti-fibrotic potential against doxorubicin-induced cardiotoxicity via the inhibition of TGFβ/SMAD2/3 pathway (Freiwan et al, 2022). However, the aptitude of mirabegron to release noradrenaline (Mo et al, 2017) may also be one possible reason behind the augmentation of SMAD-7 (Kanamaru et al, 2001).…”
Section: Injury Models Whereasmentioning
confidence: 99%
“…Formalin-fixed paraffin-embedded subvalvular areas of the left ventricles and the middle cross-sectional rings of the left kidneys were cut into 5 µm sections and were stained with hematoxylin–eosin (HE) or picrosirius red/fast green (PSFG) as described previously [ 34 , 36 , 43 , 44 ]. Histological slides were scanned with a Pannoramic Midi II scanner (3DHistech Ltd, Budapest, Hungary).…”
Section: Methodsmentioning
confidence: 99%
“…The Biology Image Analysis Software (BIAS 1.0, Single-Cell Technologies Ltd., Szeged, Hungary, https://single-cell-technologies.com/bias/ ) was used to evaluate HE images [ 34 , 36 , 43 , 44 ]. Image pre-processing was followed by deep learning-based cytoplasm segmentation.…”
Section: Methodsmentioning
confidence: 99%
“…The activation of RAAS is well-known in doxorubicin (Dox)-induced cardiac toxicity. Freiwan et al demonstrated that the simultaneous treatment of angiotensin-II receptor blocker can prevent Dox-induced cardiac diastolic dysfunction and fibrosis in rats [ 4 ]. This was accompanied by the decreased expression in interleukin (IL)-1 and-6.…”
mentioning
confidence: 99%